ART in Europe, 2017: results generated from European registries by ESHRE. Issue 3 (5th August 2021) - ,; Wyns, C; De Geyter, Ch; Calhaz-Jorge, C; Kupka, M S; Motrenko, T; Smeenk, J; Bergh, C; Tandler-Schneider, A; Rugescu, I A; Vidakovic, S; Goossens, V
Abstract: STUDY QUESTION: What are the data on ART and IUI cycles, and fertility preservation (FP) interventions reported in 2017 as compared to previous years, as well as the main trends over the years? SUMMARY ANSWER: The 21st ESHRE report on ART and IUI shows the continual increase in reported treatment cycle numbers in Europe, with a decrease in the proportion of transfers with more than one embryo causing an additional slight reduction of multiple delivery rates (DR) as well as higher pregnancy rates (PR) and DR after frozen embryo replacement (FER) compared to fresh IVF and ICSI cycles, while the number of IUI cycles increased and their outcomes remained stable. WHAT IS KNOWN ALREADY: Since 1997, ART aggregated data generated by national registries, clinics or professional societies have been gathered and analyzed by the European IVF-monitoring Consortium (EIM) and communicated in a total of 20 manuscripts published in Human Reproduction and Human Reproduction Open . STUDY DESIGN, SIZE, DURATION: Data on European medically assisted reproduction (MAR) are collected by EIM for ESHRE on a yearly basis. The data on treatments performed between 1 January and 31 December 2017 in 39 European countries were provided by either National Registries or registries based on personal initiatives of medical associations and scientific organizations. PARTICIPANTS/MATERIALS, SETTING, METHODS: Overall, 1382 clinics offering ART services in 39 countries reported a total of 940 503 treatment cycles, including 165 379 with IVF, 391 379 with ICSI, 271 476 with FER, 37 303 with preimplantation genetic testing (PGT), 69 378 with egg donation (ED), 378 with IVM of oocytes, and 5210 cycles with frozen oocyte replacement (FOR). A total of 1273 institutions reported data on 207 196 IUI cycles using either husband/partner's semen (IUI-H; n = 155 794) or donor semen (IUI-D; n = 51 402) in 30 countries and 25 countries, respectively. Thirteen countries reported 18 888 interventions for FP, including oocyte, ovarian tissue, semen and testicular tissue banking in pre- and postpubertal patients. MAIN RESULTS AND THE ROLE OF CHANCE: In 21 countries (20 in 2016) in which all ART clinics reported to the registry, 473 733 treatment cycles were registered for a total population of approximately 330 million inhabitants, allowing a best-estimate of a mean of 1435 cycles performed per million inhabitants (range: 723–3286). Amongst the 39 reporting countries, the clinical PR per aspiration and per transfer in 2017 were similar to those observed in 2016 (26.8% and 34.6% vs 28.0% and 34.8%, respectively). After ICSI the corresponding rates were also similar to those achieved in 2016 (24% and 33.5% vs 25% and 33.2% in 2016). When freeze all cycles were removed, the clinical PRs per aspiration were 30.8% and 27.5% for IVF and ICSI, respectively. After FER with embryos originating from own eggs the PR per thawing was 30.2%, which is comparable to 30.9% in 2016, and with embryos originating from donated eggs it was 41.1% (41% in 2016). After ED the PR per fresh embryo transfer was 49.2% (49.4% in 2016) and per FOR 43.3% (43.6% in 2016). In IVF and ICSI together, the trend towards the transfer of fewer embryos continues with the transfer of 1, 2, 3 and ≥4 embryos in 46.0%, 49.2%, 4.5% and in 0.3% of all treatments, respectively (corresponding to 41.5%, 51.9%. 6.2% and 0.4% in 2016). This resulted in a reduced proportion of twin DRs of 14.2% (14.9% in 2016) and stable triplet DR of 0.3%. Treatments with FER in 2017 resulted in a twin and triplet DR of 11.2% and 0.2%, respectively (vs 11.9% and 0.2% in 2016). After IUI, the DRs remained similar at 8.7% after IUI-H (8.9% in 2016) and at 12.4% after IUI-D (12.4.0% in 2016). Twin and triplet DRs after IUI-H were 8.1% and 0.3%, respectively (in 2016: 8.8% and 0.3%) and 6.9% and 0.2% after IUI-D (in 2016: 7.7% and 0.4%). Amongst 18 888 FP interventions in 13 countries, cryopreservation of ejaculated sperm (n = 11 112 vs 7877 from 11 countries in 2016) and of oocytes (n = 6588 vs 4907 from eight countries in 2016) were the most frequently reported. LIMITATIONS, REASONS FOR CAUTION: As the methods of data collection and levels of reporting vary amongst European countries, interpretation of results should remain cautious. Some countries were unable to deliver data about the number of initiated cycles and deliveries. WIDER IMPLICATIONS OF THE FINDINGS: The 21st ESHRE report on ART, IUI and FP interventions shows a continuous increase of reported treatment numbers and MAR-derived livebirths in Europe. Being already the largest data collection on MAR in Europe, efforts should continue to optimize data collection and reporting with the perspective of improved quality control, transparency and vigilance in the field of reproductive medicine. STUDY FUNDING/COMPETING INTEREST(S): The study has received no external funding and all costs are covered by ESHRE. There are no competing interests.